2014
DOI: 10.1186/2197-4284-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Lg wave propagation in the area around Japan: observations and simulations

Abstract: Regional wavefields are strongly influenced by crustal structure heterogeneity variations along their propagation paths. Observations of such effects between the Asian continent and the Japanese subduction zone across the Sea of Japan (East Sea) have been strongly assisted recently by the development of high-density seismic networks in Japan and Korea, as well as the supercomputer-based three-dimensional finite difference method seismic wave propagation simulations using detailed heterogeneous crustal models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The larger Mj values for crustal events away from subduction zones in western Japan are posited to be related to the efficient propagation of Lg-type waves in the region (Furumura and Kennett 2001). Seismic wave propagations for the 2016 event may also have been compounded by wave-guide effects due to the subducting Philippine Sea Plate in the offshore region, and Lg-type wave conversion and transmission through the inland crustal structure in southwest Japan (Furumura et al 2014). Together, all these effects contributed to the JMA magnitude being larger by 0.7 magnitude units than its F-net catalog Mw value of 5.8.…”
Section: Discussionmentioning
confidence: 99%
“…The larger Mj values for crustal events away from subduction zones in western Japan are posited to be related to the efficient propagation of Lg-type waves in the region (Furumura and Kennett 2001). Seismic wave propagations for the 2016 event may also have been compounded by wave-guide effects due to the subducting Philippine Sea Plate in the offshore region, and Lg-type wave conversion and transmission through the inland crustal structure in southwest Japan (Furumura et al 2014). Together, all these effects contributed to the JMA magnitude being larger by 0.7 magnitude units than its F-net catalog Mw value of 5.8.…”
Section: Discussionmentioning
confidence: 99%
“…Using a normal‐mode Lg representation they showed that the overall thickness of oceanic crustal waveguide is too low to allow the Lg to develop as a significant phase in the frequency band 0.3–2.0 Hz. Other researchers [e.g., Maupin , ; Shapiro et al ., ; Mendi et al ., ; Furumura et al ., ] believe simple crustal thinning at the continent‐ocean boundary alone cannot explain the observed extinction of the Lg. However, McNamara et al .…”
Section: Lg and Sn Propagationmentioning
confidence: 94%
“…Press and Ewing [] revealed that even if just a small portion of the Lg path as little as 100 km in length passes through a thin oceanic structure, Lg arrivals would be extinct on the seismogram. “Lg blockage” has been reported in many regions around the world, such as the North Sea [ Gregersen , ; Kennett and Mykkeltveit , ; Kennett et al ., ], the Caspian Sea [ Maupin , ], China [ McNamara et al ., ; Rapine et al ., ], the Himalayan Belt [ Ruzaikin et al ., ], Tibetan Plateau [ Xie , ; Fan and Lay , ], Central Asia [ Baumgardt , ], the Alpine range [ Campillo et al ., ], the oceanic region in the Sea of Japan [ Furumura and Kennett , ; Furumura et al ., ], Pyrenees [ Chazalon et al ., ], Korean Peninsula [ Hong et al ., ], and the Ligurian Sea [ Shapiro et al ., ].…”
Section: Lg and Sn Propagationmentioning
confidence: 99%
See 2 more Smart Citations